PERAN LINTAS SEKTORAL DALAM UPAYA MITIGASI PEKERJA MIGRAN INDONESIA DI PERBATASAN ENTIKONG KALIMANTAN BARAT - Alunaza, Hardi; Mentari, Mentari; Anugrah, Akhmad Rifky Setya; Iriansyah, Adibrata (UNIVERSITAS SEBELAS MARET (UNS), 2023)
Many countries have deported and repatriated migrants to reduce the spread of the Covid-19 virus. Global pandemic has effect health, economy and human rights of migrant workers. Indonesia implement to closing all gates of the country, including Entikong as on of the Border State Post area, in West Kalimantan to overcoming the impact of the pandemic. However, the policy has not been effective enough to protect security in Entikong, same as the right for social welfare and health insurance in Indonesian immigrant workers. The purpose of this study is to explore how the government and stakeholders implement the handling and protection of Indonesian migrant workers, especially in the Entikong, West Kalimantan during the Covid-19 pandemic. This paper will be explained with descriptive qualitative through the theoretical framework of border governance and AGIL Talcot Parsons with data collection techniques through interviews and literature studies obtained from journals and research report. The results of this study will emphasize the importance of the synergy carried out by the central government with local governments in the Entikong border area to mitigate Indonesian migrant workers in the Covid-19 pandemic situation for the sake of creating the security and welfare of migrants by paying attention to adaptability and adapting to the needs of the community, mutual understanding between the central and regional governments, integration of interests between stakeholders, and maintaining a pattern of good relations in achieving the interests of overcoming and mitigating Indonesian migrant workers. Keywords: Cross Sectoral, Mitigation, Indonesian Migrant Workers, Entikong. AbstrakBanyak negara yang melakukan deportasi maupun pemulangan bagi para migran demi menekan angka persebaran virus Covid-19. Pandemi global ini telah memberikan ancaman bagi kesehatan, ekonomi maupun hak asasimanusia para pekerja migran. Indonesia telah melakukan serangkaian kebijakan penutupan di seluruh gerbang masuk negara termasuk di wilayah Pos Lintas Batas Negara Entikong, Kalimantan Barat dalam mengatasi dampak dari pandemi tersebut. Namun, implementasi tersebut belum cukup efektif untuk melindungi keamanan, serta hak atas kesejahteraan sosial maupun jaminan kesehatan bagi para pekerja imigran Indonesia. Tujuan dari penelitian ini yaitu untuk mengeksplorasi bagaimana implementasi penanganan dan perlindungan pekerja migran Indonesia khususnya di Perbatasan Entikong Kalimantan Barat oleh pemerintah dan para pemangku kepentingan selama masa pandemi Covid-19. Tulisan ini akan dijelaskan dengan deskriptif kualitatif melalui kerangka teori border governance, AGIL Talcot Parsons dengan teknik pengumpulan data melalui wawancara serta studi pustaka yang didapatkan dari jurnal dan laporan penelitian. Hasil penelitian ini akan menekankan bahwa pentingnya sinergi yang dilakukan pemerintah pusat dengan pemerintah daerah di kawasan perbatasan Entikong untuk memitigasi pekerja migran Indonesia pada situasi pandemi Covid-19 demi terciptanya keamanan dan kesejahteraan migran dengan memperhatikan kemampuan adaptasi dan menyesuaikan dengan kebutuhan masyarakat, saling memahami antara pemerintah pusat dan daerah, integrasi kepentingan antara stakeholder, dan menjaga pola hubungan baik dalam pencapaian kepentingan penanggulangan dan mitigasi pekerja migran Indonesia. Kata Kunci: Lintas Sektoral, Mitigasi, Pekerja Migran Indonesia, Entikong.